RESPON PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays saccharata Sturt) TERHADAP PEMBERIAN PUPUK BOKASHI DAN PUPUK NPK - Oktofarin Aniki; Rinny Mamarimbing; Maria. G. M. Polii (Universitas Sam Ratulangi, 2018)
ABSTRACT The aim of research is study the effect of dose of Bokashi fertilizer and NPK fertilizer on the growth ant yield of sweet corn. This research has been carried out in the village Taratara districts, Tomohon West, Tomohon city, starting from January 2016 till April 2016. This research using Completely Randomized Design (RAK) consisting of six treatment and repeated as much three times so at earn eighteen plot. Such treatment is A = Without fertilizer , B = 20 tons Bokashi/ha, C = 300 kg NPK/ha, D = 200 kg NPK/ha + 20 tons Bokashi/ha, E = 300 kg NPK/ha + 20 tons Bokashi/ha, F = 400 kg NPK/ha + 20 tons Bokashi/ha. The results on variable high observation plant, number leaf, long cobs and weights of cobs, showed that giving fertilizer Bokashi and NPK do not give influence, but there is a real effect in diameter cobs. Keywords: sweet corn (Zea mays saccharata sturt), bokashi NPK